Proses Fonologis Kata-kata Bahasa Inggris yang Diucapkan oleh Orang Jepang dalam Lagu Hey Say Jump! - Heni Adnania Nugra; Agus Subiyanto (Balai Bahasa Provinsi Riau, 2022)
This study aims to find out what types of phonological processes found in pronouncing English words by Japanese native speakers and to find out the reason why the changes occur. This study is a descriptive qualitative research using transformational generative phonology’s approach. The source of data is 8 songs sung by Japanese’s idol group, Hey Say Jump! The result of the study shows that there are 8 types of phonological processes found from data analysis, they are; backing, stopping, affrication, assimilation, substitution from /l/ to /r/, epenthesis, vowel coalescence, and vowel shift. Based on the findings, it can be concluded that the phonological processes happen because of two reasons; first, Japanese has open syllable system so there is no cluster consonants and consonant sound in the final position except for /n/. Second, there are some sounds that are not present in Japanese so the sounds are adjusted according to the Japanese phonological system.